2006
DOI: 10.1186/ar1948
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Prostaglandin E2 (PGE2) plays an important role in bone development and metabolism. To interfere therapeutically in the PGE2 pathway, however, knowledge about the involved enzymes (cyclooxygenases) and receptors (PGE2 receptors) is essential. We therefore examined the production of PGE2 in cultured growth plate chondrocytes in vitro and the effects of exogenously added PGE2 on cell proliferation. Furthermore, we analysed the expression and spatial distribution of cyclooxygenase (COX)-1 and COX-2 and PGE2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 50 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Expression of these enzymes in growth plate and in normal or pathological articular chondrocytes has been detected previously [26], [56]–[59]. In rat tibia growth plates, COX-1 was strongly expressed in the reserve zone, while only moderate COX-2 expression was detected in the reserve zone [57]. In cultured rat growth plate chondrocytes, cell proliferation was inhibited by treatment with SC-236, a COX-2 selective inhibitor, but not with SC-560, a COX-1 selective inhibitor [57].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Expression of these enzymes in growth plate and in normal or pathological articular chondrocytes has been detected previously [26], [56]–[59]. In rat tibia growth plates, COX-1 was strongly expressed in the reserve zone, while only moderate COX-2 expression was detected in the reserve zone [57]. In cultured rat growth plate chondrocytes, cell proliferation was inhibited by treatment with SC-236, a COX-2 selective inhibitor, but not with SC-560, a COX-1 selective inhibitor [57].…”
Section: Discussionmentioning
confidence: 91%
“…In cultured rat growth plate chondrocytes, cell proliferation was inhibited by treatment with SC-236, a COX-2 selective inhibitor, but not with SC-560, a COX-1 selective inhibitor [57]. Proliferation of the cultured rat growth plate chondrocytes could be stimulated with PGE 2 or with a selective EP1 agonists [57]. Consistent with a COX-2 proliferative effect on growth plate chondrocytes, treatment of chicken growth plate chondrocytes with PGE 2 inhibited Type X collagen, VEGF, and MMP-13 expression indicating that PGE 2 treatment was inhibiting chondrocyte differentiation [60].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies investigating the roles of cyclooxygenases and the effects of prostaglandins on ( in vitro ) chondrogenic differentiation have mainly focussed on COX-2 (inhibition) and PGE 2 [ 14 20 ]. However, the contribution of COX-1 and other prostaglandins in chondrogenic differentiation is largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PGE 2 receptors (EP1-4) are expressed in both growth plates and primary chondrocytes [39]. Stimulation of human articular chondrocytes with PGE 2 through the EP2 receptor suppressed proteoglycan accumulation and synthesis [40].…”
Section: Discussionmentioning
confidence: 99%